The Relationship of Historical Learning Video Media With History Learning Results of Class XI Students at SMA Negeri 1 Central Lampung Rumbia 2019/2020 Academic Year - Nyoman Suwita (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2020)
ABSTRACT Education is an important thing in life. Education absolutely must be given to every human being. Therefore, teachers are required to be able to design and implement learning experience programs appropriately so that students gain complete knowledge so that the learning process becomes meaningful for students. The formulation of the problem in this research is "How is the relationship between video media and student learning outcomes in history subjects in Class XI SMA N 1 Rumbia for the 2019/2020 academic year?" The purpose of this study was to find out "how is the relationship between video media and student learning outcomes in history subjects for class XI at SMA N 1 Rumbia for the 2019/2020 academic year?". This study used a Posttest-Only Control Design research design. The population in this study were students of class XI IPS 2 and XI IPS 4. Purposive sampling is a technique used to determine the sample in this study. This technique is carried out on the entire population, but focused on the target. The data analysis technique in this research is quantitative data analysis by means of data analysis using Alpha formula. Keywords: Relationships, Video Media, Learning OutcomesDoi: http://dx.doi.org/10.23960/pesagi.v8.i2.2020.03